Predation efficacy of Chrysoperla carnea on two economically important stink bugs - Olivier Hendrik Berteloot; Gertie Peusens; Tim Beliën; Thomas Van Leeuwen; Patrick De Clercq (Biological Control)
Larvae of the green lacewing Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) are generalist predators feeding on a range of pests in agroecosystems. Little is known about the suitability of stink bugs as prey for lacewing larvae. In the present laboratory study, the predatory efficacy of C. carnea on two economically important stink bugs, Halyomorpha halys (Stål) and Nezara viridula (L.) (Hemiptera: Pentatomidae), was evaluated at three constant temperatures (16, 21, and 26 °C) in different arenas (10-cm diameter dishes with bean pod slices or caged small bean plants). We found that second and third instars of C. carnea readily prey on the first instars of both stink bug species. However, only third instars of C. carnea could successfully kill and feed on second instars of either pentatomid. The complexity of the arena, as well as the life stage of the prey and predator influenced the predation efficacy of C. carnea on stink bug nymphs, whereas temperature did not. The observed predation rates on the early instars of both stink bugs suggest that augmentative releases of C. carnea larvae may have some potential in greenhouse crops, particularly against N. viridula infestations, whereas in open field crops their natural populations may also contribute to pest suppression within the broader predator guild.